INSTAGRAM AS COGNITIVE LEARNING ASSESSMENT TOOL: OPPORTUNITIES AND CHALLENGES - Rahayu, Dini Puji; Purnamanita, Eka Ismaya Indra (Proceeding of International Conference on Islamic Education (ICIED), 2021)
Instagram is one of the popular social media, with the most users aged 18-24 years. The features provided by Instagram are varied and interesting, enabling learning assessments to be carried out using these social media. Looking at the traditional learning assessment so far, this study intends to examine the opportunities and challenges of Instagram when used in cognitive learning assessments. The approach and type of research used is a qualitative approach, with the type of literature study. The data that became the source were several documents, books, and scientific literature. The results of this study show the opportunities of using Instagram as a cognitive assessment tool are: 1. Multimedia-based Instagram is more interesting to use as a cognitive assessment tool; 2. Using Instagram as a cognitive assessment tool can improve ICT skills for students and teachers; 3. Easy to analyze learning assessment data on Instagram; 4. It becomes simple if Instagram is used both as an assessment tool and class activities; 5. Instagram features are easy to use in supporting learning assessments; 6. Prompt feedback from the assessment in various formats. While the challenges are: 1. Educator skills in adjusting Instagram features with the form of learning assessment; 2. Changes to Instagram's policy require adaptation for its users; 3. The need for a computer or mobile phone with good internet access; 4. Minimum age limit for Instagram users; 5. Ensure that students have good academic integrity during the learning assessment.